2015
DOI: 10.5539/mas.v9n5p114
|View full text |Cite
|
Sign up to set email alerts
|

Intensification Dissolved Air Flotation Treatment of Oil-Containing Wastewater

Abstract: The paper is devoted to the oil-containing water treatment by dissolved air flotation. Patents search revealed trends in the dissolved air flotation devices development. A method for increasing the treated fluid aeration by its dispersion at excess pressure is offered.The electrolyte influence on the flotation extraction efficiency is researched. The change in electrolyte concentration influences the bubble coalescence degree, as well as the charge on the particle and the bubble. It is shown that an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the other hand, large bubbles tend to rise rapidly, which results to lower collision efficiency. It was also reported that bubble sizes decrease with salinity (Eskin et al, 2015). Hence, better separation efficiency can be expected in saline water.…”
Section: Oil Droplet and Bubble Sizementioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, large bubbles tend to rise rapidly, which results to lower collision efficiency. It was also reported that bubble sizes decrease with salinity (Eskin et al, 2015). Hence, better separation efficiency can be expected in saline water.…”
Section: Oil Droplet and Bubble Sizementioning
confidence: 94%
“…Current developments of flotation systems focus on the followings (Eskin et al, 2015):-(i) Reduction of aeration time (e.g. pressure vessel with porous media partition, pressure accumulator, electric discharge method, DAF pump and etc.)…”
Section: Latest Development In Gas Flotationmentioning
confidence: 99%
“…EF is a wastewater treatment process using fine hydrogen and oxygen bubbles that are generated by electrolytic decomposition of aqueous solutions as illustrated in Fig. 12 (Eskin et al 2015). Oxygen is generated at the anode electrode due to the oxidation of water (eq.…”
Section: Electrolytic Flotationmentioning
confidence: 99%
“…According to this, one of the dissolved air flotation development tendencies is saturation time reduction with simultaneous raise of concentration of air dissolved in liquid. The existing methods of efficiency improvement of dissolved air flotation were studied in the research by Eskin et al [5]. The researchers of the Department of Buildings and Constructions Engineering Systems at Far Eastern Federal University introduced a method and an experimental setup ( Fig.…”
Section: Liquid Atomization Under Dissolved Air Flotationmentioning
confidence: 99%